Clinical and Radiological Findings of Mandibular Cystic Lesions - Lovekesh Kumar; Suneel Kumar Punjabi; Sikander Munir Memon; Hira Yousuf; Shuja Aslam (JLUMHS, 2018)
OBJECTIVE: To determine the clinical and radiological findings of mandibular cystic lesions. METHODOLOGY: This study was descriptive case series, conducted on 40 cases of mandibular cystic lesions at Oral & Maxillofacial Surgery Department, Liaquat University of Medical & Health Sciences, Jamshoro / Hyderabad from December 2015 to November 2016. Usually intraoral radiographs were done for radiological finding and CT scans where required for examining the extension of mandibular cyst. Among the features recorded on radiographs were involvement of the local anatomical structures, appearance of the cyst as multilocular or unilocular, root resorption of adjacent teeth and size. Data was analyzed by statistical software package SPSS version 20.0. RESULTS: During the study period, a total of 40 patients with clinico-radiographic and histopathological finding of mandibular cystic were included. Radiographically most radicular cysts 34(85.0%) appear as round unilocular radiolucent lesions in the periapical region. The most common type of cysts observed in the study were radicular cyst in 21 cases (14 males and 07 females) followed by dentigerous cyst in 11 (27.5%) cases, odontogenic keratocyst in 5(12.5%) cases. Median mandibular cyst and others respectively. The main finding in this study was that there was no association or insignificant difference of types of cysts with age and gender. These types of cysts may occur equally in bother male and female (p value > 0.05). CONCLUSION: Evaluation of the results of this study shows that radicular cyst is the most common odontogenic cyst, coincident with the prevalence of dental caries.